Unveiling the Impact of Mobile Fitness Applications on Motivational Orientation in Sustaining Exercise Behaviors: A Qualitative Investigation - Southcott Evé; Jooste Julius (Sciendo, 2024)
Notably, a lack of motivation appears as a significant contributing factor to physical inactivity, which raises one's susceptibility to noncommunicable diseases. While research indicates a strong link between smartphone fitness applications (apps) and people's motivational orientation towards physical activity and exercise, the theoretical basis of fitness app features for sustaining exercise routines remains unclear. Therefore, the purpose of this study was to investigate the utility of fitness apps as a behaviour modification tool on people's motivation to maintain physical activity and exercise behaviour. Using individual semi-structured interviews, we collected detailed accounts from nine active male and female fitness app users (Mage = 23.4 years, SD = 2.8). The findings of both inductive and deductive reflective thematic analysis revealed core themes emphasising that the use of fitness apps satisfies the participants' psychological needs through fostering emotions of competence, autonomy, and relatedness. Furthermore, fitness apps make it easier to track progress, challenge oneself, and compete against other exercisers, which further motivates participants to sustain their exercise behaviours. Confirming the use of fitness apps as an effective behaviour change tool for sustaining healthy exercise routines, the findings offer valuable feedback on specific app features for fitness software and wearable device developers that could potentially enhance the functionality and impact of their apps. Further discussions include limitations and areas for future research, such as discerning the role of fitness apps in sustaining motivation among diverse age groups with specific health, sport, or lifestyle goals in varying sensory, social, and affective contexts.